Regulation of executive directors remuneration in South Africa : the road to achieving good corporate governance - Asafo-Adjei, Marang Akua (Department of Commercial Law, 2015)
The purpose of this dissertation is thus to evaluate the extent to which the existing legal and regulatory instruments in South Africa have effectively regulated director’s remuneration as a means of ensuring that those in control are accountable to the owners and do not remunerate themselves excessively with the owners’ money. The research will embark on a comparative analysis with international jurisdictions being Australia and the United Kingdom with the objective of determining how these countries have regulated executive director remuneration and the lessons that South Africa can learn from them. Lastly, the research will provide recommendations on how the existing framework s can be improved to ensure adequate and effective regulation of executive director remuneration.